358 CURRENT PREDICTORS OF BLEEDING AFTER PERCUTANEOUS KIDNEY BIOPSY. Issue 1 (1st January 2007) - Miller, R. E.; Islam, N.; Mire, C.; Schmidt, D.; Fulop, T.
Abstract : Background: Patients with advanced chronic kidney disease (CKD) are felt to have an acquired platelet dysfunction and an increased risk of bleeding during invasive procedures. This report summarizes our ongoing experience with clinical and laboratory predictors of bleeding risk during percutaneous native and transplant kidney biopsies. Methods: Prospective cohort study so far enrolling 41 patients undergoing renal biopsy, designed to assess clinical utility of PFA-100. Baseline data included age, sex, weight, BMI, blood pressure (BP), serum chemistry, CBC, urine studies, PT/PTT, and PFA-100 (Platelet Function Analyser-100). BMI ranged from 18 to 40 and BP ranged from 105 to 170 mm Hg systolic and 60 to 102 mm Hg diastolic. Desmopressin acetate (DDAVP) was routinely given if the GFR predicted < 30 mL/min/1.73 m 2 . Trainee physicians performed renal biopsies under real-time ultrasound (US) guidance using a 16-gauge, spring-loaded biopsy needle. Main outcomes included hematuria, hematoma formation, and need for transfusion. Follow-up renal US in 24 hours was evaluated for hematoma formation. Data were analyzed using SPSS -13 for descriptive statistics and ANOVA. Results: Nine patients had postbiopsy hematoma formation on US but only two required transfusion. No patient experienced death, loss of a kidney, or need for surgical intervention. Of the patient-related variables collected, only 4-hour postprocedure MAP was found to be associated with bleeding complications (hematoma formation, p = .042; transfusion requirement p = .023). Of the procedure-related variables collected, only the number of passes was associated with bleeding complications (need for transfusion, p = .006). There was remarkable little correlation between bleeding risk and baseline characteristics. An abnormal PFA-100 did not affect any of the bleeding complications studied. Within the range of inclusion criteria, neither BMI nor baseline BP correlated with bleeding events. Risk of bleeding complications was not associated with GFR, suggesting that when DDAVP is routinely given if GFR< 30 mL/min/1.73 m 2, the bleeding risk is independent of renal function. Conclusion: (1) Percutaneous kidney biopsy under direct US visualization remains a safe procedure under a wide range of BP and BMI variations and an essential element of nephrology training. (2) Most hematomas observed on US did not require transfusion. (3) Four-hour postbiopsy MAP correctly predicted hematoma formation and the need for blood transfusion. (4) Abnormal PFA-100 did not appear to predict bleeding in the current database.